Determining the age of documents based on the stamp and seal impression - Busarčević, Miroslav; Simonović, Branislav (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The present article discusses determining the age of a document based on a comparative analysis of the stamp impression in the questioned documents and an authentic document. The aim of the paper is to show that classical traceology methods are easily applied in judicial practice. Based on the analyzed instances of judicial practice, themain conclusion of the paper is that typical analysis of the stamp impression can precisely show the time frame for when the questioned document was created – no expensive and complex physicochemical laboratory analysis methods are necessary.
Keywords: determining the age of the document based on the stamp impression; comparative analysis of the stamp impression; general, individual, and identifying characteristics